Evaluasi Kualitas Kinerja SAP (Systems, Applications, And Products in Data Processing) dengan Pendekatan CIPP (Context, Input, Process, Product) - Sandi Gita Wibawanti (Universitas Serambi Mekkah, 2026)
This study aims to evaluate the performance quality of the SAP (Systems, Applications, and Products in Data Processing) system in supporting logistics and supply chain operations at PT XYZ using the CIPP (Context, Input, Process, Product) approach. This research employs a qualitative method with an evaluative approach to gain an in-depth understanding of SAP implementation within the company. The unit of analysis includes the SAP system and its users, particularly those involved in logistics and purchasing activities. Data collection techniques consist of observation, interviews, and documentation, while data analysis is conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that SAP implementation at PT XYZ is generally aligned with operational needs and has contributed to improving work efficiency, data integration across departments, and real-time information availability for decision-making. However, the system utilization has not been fully optimized due to several constraints, particularly related to human resource readiness, including the lack of standardized and evenly distributed training, as well as inconsistent system usage among employees. Additionally, reliance on manual processes in certain conditions still affects overall system effectiveness. Based on these findings, this study recommends enhancing structured and continuous training programs, strengthening system governance, and optimizing SAP features to better adapt to operational needs. These improvements are expected to maximize the benefits and sustainability of SAP implementation in improving organizational performance.